Dorper sheep in Africa: A review of their use and performance in different environments - Ojango, Julie M.K.; Okpeku, M.; Osei-Amponsah, R.; Kugonza, D.R.; Okeyo Mwai, Ally; Chagunda, Mizeck G.G.; Olori, V.E. (CAB International, 2023)
The Dorper breed developed in South Africa is used either as a pure breed or crossbred with existing indigenous breeds by many countries across the African continent to improve sheep production. This article presents documented information on the adoption, use, and performance of Dorper sheep across the continent of Africa and opportunities for their more sustainable production under the changing climatic conditions in Africa. Apart from the well-documented information on the Dorper sheep in South Africa, published information on the performance of the sheep is mainly from Eastern Africa. Most countries initially retained purebred Dorpers in nationally owned institutions for multiplication and crossbreeding trials with different indigenous breeds prior to distributing the crossbreds to diverse livestock keepers. The offspring produced through crossbreeding programs with the Dorper have better growth rates than indigenous breeds in the different countries; however, the performance of Dorper sheep in South Africa has not been achieved in any of the other countries. Genomic studies including Dorper sheep have identified regions of interest for resistance to brucellosis and Mycoplasma ovipneumonia that imply adaptability to challenging environments within Dorper sheep. Unfortunately, limitations in systems for guided breeding and monitoring of sheep productivity in Africa have resulted in haphazard crossbreeding of the Dorper. Targeted efforts are required across the different countries to develop breeding programs for improving locally adapted Dorper sheep populations and their crosses with indigenous breeds. New science and technologies need to be innovatively packaged and used to identify and propagate more productive and resilient Dorper and Dorper-based breed-types for the increasingly challenging tropical African range environments.